Negotiating AI in academic writing: Student voices on autonomy, ethics, and process-based learning - Lutviana, Rizky; Sulistyo, Teguh; Purnawati, Maria (Edelweiss Applied Science and Technology, 2026)
The adoption of Artificial Intelligence (AI) in academic writing has been widely discussed in terms of its impact on writing performance and efficiency, with little attention given to how students actively negotiate its place in process-oriented pedagogies. To fill this gap, this paper investigates how university students negotiate autonomy, ethical responsibility, and cognitive engagement in the context of integrating AI into a Process-Based Approach (PBA) to academic writing. A qualitative-dominant mixed-method design was used. Data were collected from 103 students from eight universities in Indonesia using four Likert-scale questionnaires and open-ended responses, and analysed using descriptive statistics and thematic analysis. Findings suggest that AI is perceived as a form of cognitive support for lower-order writing processes, such as grammar, vocabulary, and idea generation, while students aim to retain control. However, support also produces tensions of overreliance, reduced critical participation, and challenges to academic integrity. Students are beginning to understand the ethical limits, especially when it comes to AI being a tool that helps them with their own writing rather than replacing it. The findings indicate that AI-mediated writing is not only a matter of tool use but a site of negotiation, in which learners negotiate efficiency, autonomy, and authenticity.